The Nutrition Support Team - Duna Penn (Paediatrica Indonesiana, 1997)
The development of nutrition support teams in the United States was stimulated in the 1970's and 80’s by reports concerning the prevalence and consequences of malnutrition among hospitalized patients. Butterworth's provocative paper, "The skeleton in the hospital closet"1 was followed by several nutrition surveys of relatively large numbers of in-hospital patients that documented abnormal anthropometric and laboratory measurements indicating suspected malnutrition in 44-58% of adult medical'11 and surgical patients. '1 Up to a third of non-neonatal pediatric patients were found to have evidence of malnutrition in 2 major studies."'7 This malnutrition was associated with longer hospital stays, increased morbidity and mortality.2“9 Of particular significance was the reported deterioration of nutritional status with prolonged (> 14 days) hospital stay. In one study," nutritional parameters worsened in over 75% of patients who had been admitted with normal values. While it was clear that malnutrition was in part due to underlying disease, it was also clear that it was in part iatrogenic (Table 1).